Spatial Orientations of Angular Momentum Vectors of Galaxies in Supercluster S [247+040+0029] and Substructures - Malla, J. R.; Saurer, W.; Aryal, B. (Journal of Nepal Physical Society, 2021)
We present an analysis of spatial orientations of 1331 galaxies in the supercluster S [247+040+0029]. The main goal of this work is to search for a new substructure candidate and examine the orientation of angular momentum in the framework of three different scenarios (hierarchy, pancake, and primordial vorticity models) using “position angle-inclination method”, and to test the dependence on magnitude with the angular momentum orientations and their projections. We identified five substructures studying number density contour map with considerably high concentration of galaxies. Using random simulation method to remove the selection effect on database, we carried out expected isotropic distribution using cosmological principle. We then used three statistical tests: Chi-square, Auto-correlation, and Fourier to identify isotropy between observed and expected isotropic distributions. We varied radius in the range 0.3° to 1.0° to find substructures in supercluster. From this we found five sub-structures when taking radius 0.3° and two substructures for 1.0° radius in the number density counter maps of galaxies. By analyzing the result obtained through statistical tests, we are able to conform that evolution of galaxy in the supercluster and substructures supports “Hierarchy model" giving the angular momentum of galaxies in the large scale structure tends to be oriented random with respect to the reference coordinate system.